If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3=12y-5(2y+7)
We move all terms to the left:
-3-(12y-5(2y+7))=0
We calculate terms in parentheses: -(12y-5(2y+7)), so:We get rid of parentheses
12y-5(2y+7)
We multiply parentheses
12y-10y-35
We add all the numbers together, and all the variables
2y-35
Back to the equation:
-(2y-35)
-2y+35-3=0
We add all the numbers together, and all the variables
-2y+32=0
We move all terms containing y to the left, all other terms to the right
-2y=-32
y=-32/-2
y=+16
| -9=-3(n=5) | | 2e−12=7e+8 | | 7(2y+6)=-7y | | -2/3g=-22 | | 55+30+55+30-5=x | | -6+6p=-90 | | 10(x/1)=7(x/4) | | 6+19-4=5(5x+4) | | X+30+x+30-5=x | | 10(x+1)=7(x/4) | | 4.3x+(66.3/59.659)=33.07 | | (3)/(x)=(9)/(4x)+3 | | 3x-4x=43 | | 2x+5(5x-7)=47 | | 13+2(x-6)=19-3(x+1) | | 2.1(z+1)-3.6=6.27 | | 2x+9=(2x+9)(2x+9) | | x(3x-9)=(3x+6)(x-7) | | u+3.2=6.3 | | -(3x+2)+5=-2+1+9x | | 1.56(c+5)+9.97=5.29 | | –6+3m=4m | | r-4.7=3.1 | | 3x-15=8x+25 | | k^2-k+48=0 | | 20-x2=16 | | 3(2x-5)=4x-9 | | 6=-w|8 | | 08r=64 | | 4x-2(4x+30)=16x | | 9(3c-1)+4=49 | | 2y+9.9=1.1 |